Screening and quantifying the quality markers of DuHuo by fingerprint modeling. Issue 15 (1st October 2020) - Yang, Liu; Hou, Ajiao; Sun, Yanping; Wang, Song; Zhang, Jiaxu; Jiang, Hai
Abstract: With environmental health and safety becoming a concern for people, supercritical fluid chromatography has been regarded as a "green chemistry" method that gradually has peaked people's interest. The purpose of this study was to establish a method to screen and quantify the quality markers of Duhuo (DH) through an environmentally friendly ultra-performance convergence chromatography (UPC 2 ) method. Firstly, the fingerprint of different batches of DH samples was established by UPC 2 . Then, the quality markers that can represent the whole information of DH was screened through chemometrics. Finally, the content of the selected quality markers was determined using the UPC 2 method. From the fingerprint analysis, 24 common peaks were identified. The quantitative analysis results showed that the four compounds could be used as quality markers to represent the overall information and to monitor the quality of DH. This is the first time a traditional Chinese medicine (TCM) fingerprint has been established by UPC 2 and also the first time to screen the quality markers in DH. The method established in this study can be used for a comprehensive and overall analysis of DH or other natural medicines, and it could serve as an efficient method to contribute to the expansion of the global market for TCMs. Graphical Abstract: